Rwanda One Health achievements and challenges: The final push toward policy implementation - Shyaka, Anselme; Igihozo, Gloria; Tegli, M.; Ntiyaduhanye, Esther; Ndizeye, Elisee; Umuhoza, Ange; Knight-Jones, Theodore J.D.; Richards, Shauna (CAB International, 2024)
The Rwanda Government has adopted the One Health (OH) approach to ensure optimal preparedness and response to complex health challenges. Despite the approach adopted by government institutions, academia, and other stakeholders, there are few insights into the status of OH research and innovation, education, governance, and implementation of OH solutions. The Capacitating OH in Eastern and Southern Africa (COHESA) project aims to enhance the capacity of local institutions to bring about optimal solutions to OH challenges. This case report aimed to provide baseline information about the adoption and implementation status of Rwanda’s research and innovation, governance, and education related to the OH approach. An evaluation tool collected baseline information from selected institutions’ representatives in key informant interviews and focus group discussions. Moreover, a review of grey and published literature on One Health in Rwanda was conducted. A wide range of actors, including parastatal institutions, academia, NGOs, and private sectors, are involved in OH activities in Rwanda. Various institutions of higher learning education mainly use extracurricular activities to deliver OH education. However, the University of Global Health Equity has adopted an innovative approach to OH education by integrating OH in the medical curriculum and implementing a graduate degree with an OH concentration. Rwanda is among the few countries with an OH policy that is essential to guide actions and distribute responsibilities among various actors. However, anchoring the unit responsible for OH governance in the prime minister’s office could boost OH institutionalization and facilitate coordination and collaboration among OH stakeholders.